1995
DOI: 10.1007/bf00997243
|View full text |Cite
|
Sign up to set email alerts
|

Brain single-photon emission tomography with99mTc-HMPAO in neuropsychiatric systemic lupus erythematosus: relations with EEG and MRI findings and clinical manifestations

Abstract: Central nervous system (CNS) involvement in patients with systemic lupus erythematosus (SLE) is often difficult to evaluate because of protean neuropsychiatric (NP) manifestations and lack of reliable diagnostic markers. In the reported study the role of single-photon emission tomography (SPET) with technetium-99m hexamethylpropylene amine oxime (HMPAO) in the evaluation of CNS involvement in SLE was assessed and the relations between SPET perfusion defects, EEG examination, magnetic resonance imaging (MRI) fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 30 publications
0
33
0
5
Order By: Relevance
“…To date, no significant associations or correlations between (regional) CBF and NP involvement have been reported (8,(10)(11)(12)(13)(14)(15). Rubbert et al (13) reported that they did not find any association between clinical SLE manifestations and also found no relation between CBF observations and NP symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, no significant associations or correlations between (regional) CBF and NP involvement have been reported (8,(10)(11)(12)(13)(14)(15). Rubbert et al (13) reported that they did not find any association between clinical SLE manifestations and also found no relation between CBF observations and NP symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, they found no correlation with overall disease activity or serological disease parameters and poor correlation with the expert NP diagnosis. So far, no significant associations or correlations between (regional) CBF and NP involvement have been reported (8,(10)(11)(12)(13)(14)(15). To our knowledge, no perfusion weighted MR studies are available in NPSLE patients to date.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 97%
See 1 more Smart Citation
“…Approximately 40% of the NP-SLE manifestations develop before the onset of SLE or at the time of diagnosis and about 60% within the first year after diagnosis (van Dam, 1991). While a histologically normal brain with no specific pathognomonic brain lesions is a possible finding in NP-SLE, various abnormalities include hypoperfusion (Colamussi et al, 1995;Handa et al, 2003;Huang et al, 2002;Lopez-Longo et al, 2003) and regional metabolic abnormalities (Komatsu et al, 1999;Sibbitt and Sibbitt, 1993;Brooks et al, 1997;Volkow et al, 1988). Brain atrophy, however, is the most frequent observation on CT scans (Gonzalez-Scarano et al, 1979;Kaell et al, 1986;Miguel et al, 1994;Omdal et al, 1989;Ainiala et al, 2005;Waterloo et al, 1999) and is proposed to reflect widespread and progressive neuronal loss (Sibbitt and Sibbitt, 1993;Sibbitt et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Neurologic and psychiatric (NP) manifestations of unknown etiology are common in SLE and have been proposed to represent a more severe form of the disease, often denoting a graver prognosis (Bombardier et al, 1992;Rubin et al, 1985). Contemporary imaging techniques indicate that profound metabolic alterations and neuronal loss accompany neuropsychiatric lupus, or NP-SLE (Colamussi et al, 1995;Sibbitt et al, 1994). Periventricular lesions, cerebral atrophy, and ventricular enlargement of unknown etiology occur in up to 50% of patients (Baum et al, 1993;Bosma et al, 2000).…”
Section: Introductionmentioning
confidence: 99%